al Sayid 'Uthman ibn Yahyà Mufti Batavia wa Juhūduh fi Khidmati al Sunnah fi Jakarta - Mustaghfirin, M. Khairul (Center for Research and Development of Religious Literature and Heritage, 2022)
This article discuss about the uniq and important information of Sayyid Usman bin Yahya contribution as one famous Scholar Muslims in Nusantara specialy for Muslim Society in capital Country of Jakarta untill called by “Mufti of Batavia” wich done by maintaining tradition and Islamic culture methode of sanad. It enables that the teaching delivered in continued to the authors of book (kitab) up to prophet Muhammad (peace be upon him). The Muslim Scholars like Sayyid Utsman bin Yahya still attand and maintains about sanad tradition and based on teaching learning system. This article explains to the urgency of Islamic references wich Nusantara scholar writings and ideas product in religious knowledge affairs specialy for nusantara Scholers. This article is qualitative research. After the data was collected with heuristics, it was analyzed by source criticism, interpretation, and historiography with help by Ulumul Hadis or Hadis sains, so this study uses qualitative approach and data collected through observations not use Quantitative approach because this discussion and topic is social and relegion case. This results found that This historiography reveals the transmission of Islamic knowledge specialy for Hadist and it saince which the Scholars muslim like Sayyid Usman “Mufti Betawi” attend the sanad and lisence tradition, also that Sayyid Ustman one of Hadis Scholars because his books is mention about hadis sains. Sayydi Ustman is Interdisiplines sains, and take care the sunah tradition and civilation, proven by his essays and writing of Hadis literature.